Genetic differences between strains of Biomphalaria glabrata (Planorbidae) that are susceptible and unsusceptible to schistosomiasis - Oliveira, A. L. D. [UNESP]; Da Silva, D. [UNESP]; Manzano, B. C. [UNESP]; Abdel-Hamid, A. Z.; Marcelino, M. Y.; Zanotti-Magalhaes, E. M.; Magalhaes, L. A.; Ribeiro-Paes, J. T. [UNESP] (Funpec-editora, 2010)
Despite the implementation control programs, schistosomiasis continues to spread throughout the world. Among modern control strategies, vector control is currently being emphasized. Within this context, analysis of the genetic variability of intermediate host snails (Biomphalaria spp) is important because it allows identification of specific sequences of the genome of this mollusk related to susceptibility/resistance to Schistosoma mansoni infection. We investigated Brazilian albino (non-pigmented) and pigmented (wild type) strains of Biomphalaria glabrata; these strains differ in their susceptibility to S. mansoni infection. Genetic variability was studied by RAPD-PCR using different random primers. The electrophoretic patterns resulting from amplification showed specific polymorphic markers for the albino and pigmented strains of B. glabrata. This information will help in the identification and isolation of genes specifically related to susceptibility, demonstrating that RAPD-PCR is an appropriate and efficient methodological approach for analysis of the genetic variability of schistosomiasis vectors.
Keywords: Schistosoma mansoni; Biomphalaria; Polymorphism; Genetic variability; RAPD-PCR